Instructional Perseverance in Early-Childhood Classrooms: Supporting Children's Development of STEM Reasoning in a Social Justice Context - Jennifer Ward; Joseph DiNapoli; Katie Monahan (MDPI AG, 2022)
In early childhood education (ECE) classrooms, teachers navigate practices about how to allow space for students to make sense of new STEM-based ideas. We posit that such pedagogical moves require ample in-the-moment perseverance by the instructor. In this paper, we seek to explore the nature of such instructional perseverance in ECE classrooms and how it manifests when ECE educators are supporting young children to develop their STEM reasoning, with a primary focus on the mathematics discipline in a social justice context. Working with a dataset consisting of four ECE classroom episodes, we employed an analytical framework that captured evidence of instructional perseverance. We found that the instructional perseverance of the ECE teacher was integral to the development of STEM reasoning of her young students. We present an illustrative case that details the instructional perseverance of the ECE teacher and the related STEM reasoning of her students in the context of exploring income variance by race. We argue that teacher education development must address how ECE teachers can plan for and navigate in-the-moment instructional obstacles in order to support young students' STEM reasoning development, which positions students for productive STEM-based outcomes.